2009
DOI: 10.1614/wt-08-050.1
|View full text |Cite
|
Sign up to set email alerts
|

Peanut and Eclipta (Eclipta prostrata) Response to Flumioxazin

Abstract: Research was conducted in North Carolina to determine peanut response to flumioxazin as influenced by rate and timing of application and cultivar. Delaying application of flumioxazin from 1 d after planting until peanut emergence increased injury regardless of rate. The Virginia market-type cultivar ‘NC-V 11’ was injured more by flumioxazin than the cultivars ‘Gregory’ or ‘Perry’. However, pod yield was not affected by flumioxazin even though significant injury was observed early in the season regardless of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
7
1
Order By: Relevance
“…They concluded if given ample time to compensate for delays in maturity, peanut yield should not be affected. Similar results were also reported by Jordan et al (2009) in which they found that delaying the application of flumioxazin until peanut emergence increased injury regardless of rate but pod yield was not affected.…”
Section: Peanut Yield Responsesupporting
confidence: 88%
See 1 more Smart Citation
“…They concluded if given ample time to compensate for delays in maturity, peanut yield should not be affected. Similar results were also reported by Jordan et al (2009) in which they found that delaying the application of flumioxazin until peanut emergence increased injury regardless of rate but pod yield was not affected.…”
Section: Peanut Yield Responsesupporting
confidence: 88%
“…), prickly sida (Sida spinosa L.), and Florida beggarweed (Desmodium tortuosum (Sw.) DC) (Wilcut, 1997) while in Texas, pitted morningglory [Ipomoea lacunosa L.] were controlled greater than 75% (Grichar and Colburn, 1996). Flumioxazin has been reported to cause peanut injury especially when the application is delayed until peanut emergence (Johnson et al, 2006;Jordan et al, 2009;Tredaway-Ducar et al, 2009). When applied soon after peanut planting (1 to 2 d), Grichar et al (2004) reported that flumioxazin plus metolachlor combinations, under cool, wet conditions resulted in peanut stunting which was evident throughout the growing season.…”
mentioning
confidence: 99%
“…Flumioxazin can injure peanut, especially when the application is delayed until peanut emergence (Johnson et al, 2006;Jordan et al, 2009;TredawayDucar et al, 2009). When applied soon after peanut planting (1 to 2 d), Grichar et al (2004) reported that flumioxazin plus metolachlor combinations, under cool, wet conditions resulted in peanut stunting which was evident throughout the growing season.…”
Section: Resultsmentioning
confidence: 99%
“…Bukun (2011) aggregated that the number of red root pigweed (Amaranthus retroflexus) for 5 plants/m 2 showed the maximum of the yield loss percentages against peanut (Arachis hypogoea) for 70%, while the number of red root pigweed (A. retroflexus) for 1 plants/m 2 exhibited the minimum of the yield loss percentages against peanut (A. hypogoea) for 25%. Jordan et al (2009) comprehended that the peanut (A.…”
Section: Introductionmentioning
confidence: 99%